THE POTENCY OF SOURSOP LEAF WATER EXTRACT ON ACTIVATING GLP-1R, INHIBITING DPP4 AND FOXO1 PROTEIN BASED ON IN SILICO ANALYSIS - DAMAYANTI, DINI SRI; NURDIANA; KUSUMA, H. M. S. CHANDRA; SOEADMADJI, DJOKO WAHONO (International Journal of Applied Pharmaceutics, 2019)
Objective: Soursop leaf contains alkaloids, terpenoids, flavonoids, acetogenin, and phenolics. Soursop leaf decoction is usually consumed as an anti-obesity agent, even though its active compounds and its action mechanism are still unclear. Computational approaches have been developed to predict the ability of an active compound to bring about biological effects. This study was designed to predict the potency of soursop (Annona muricata Linn.) water extract for the activating of Glucagon-Like Peptide-1 Receptor (GLP-1R), Inhibiting Dipeptidyl Peptidase 4 (DPP4), and Forkhead Box Protein O1 (FoxO1) protein using in silico analysis. Methods: Identification of active compounds contained in soursop leaf water extract was carried out using physicochemical methods and Gas chromatography–mass spectrometry (GC-MS). They were then analyzed using computational analysis, i.e., potential analysis using the Way2drug web server. Protein interaction predictions of GLP-1R with the active compounds found in soursop leaf water extract using STITCH. The affinities of the active compounds of soursop leaf to the proteins DPP4 and FoxO1 were also analyzed using molecular docking. Results: Active compounds of the soursop leaf water extract contain 5-isopropenyl-3,8-dimethyl-1,2,3,3A, 4,5,6,7-octa hydro azulene (22.17%) and 1,2-benzene dicarboxylic acid, diethyl ester (phthalic acid) (57.30%). The active ingredients have not been shown to interact with GLP-1R. 5-isopropenyl-3,8-dimethyl-1,2,3,3A, 4,5,6,7-octa hydro azulene and phthalic acid both have a weak affinity for DPP4, and only phthalic acid has a weak affinity with the FoxO1 protein. Conclusion: Phthalic acid has a weak potential as an inhibitor of the DDP4 and FoxO1 proteins.